Reaction of pentacarbonyliron with a nitrogen heterocycle. X-ray crystal structure of bis[(carbonyl)(quinoline-2-thiolate-N,S)]iron(II) - Mauro, A. E. [UNESP]; Casagrande, O. L. [UNESP]; Nogueira, V. M. [UNESP]; Santos, R. H. A.; Gambardella, M. T. P.; Lechat, J. R.; Filho, M. F. J. (Elsevier B.V., 1993)
The monomeric compound bis[(carbonyl)(quinoline-2-thiolate-N,S)]iron(II) was synthesized and studied by IR and Mossbauer spectroscopy, cyclic voltammetry and X-ray diffraction. The molecule has two terminal carbonyl groups and two quinoline-2-thiolate anions coordinated as N,S-donor chelates, and the iron atom shows an octahedral coordination geometry.